Pengaruh Kondisi Keuangan Perusahaan Dan Profitabilitas Terhadap Penerbitan Opini Audit Going Concern Pada Industri Tekstil Dan Garmen Di Bursa Efek Indonesia - Eja Armaz Hardi; G.W.I Awal Habibah; Arif Rahman Ramadhan (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2023)
This study aims to determine how the influence of the company's financial condition and profitability on the issuance of going concern audit opinions on the Indonesia Stock Exchange (IDX). This study uses quantitative methods. The data analysis method is using Logistic Regression. The sample used in this study is the financial statements of the textile and garment industry listed on the IDX for the period 2018 to 2021. The results of this study indicate that the company's financial condition has a significant and negative effect on the issuance of going concern audit opinions, profitability has no significant and positive effect on the issuance of Going concern audit opinion as well as the company's financial condition and profitability have no significant simultaneous effect on the issuance of going concern audit opinion. Keywords: company's financial condition, profitability, issuance of going concern audit opinion